2020
DOI: 10.1016/j.engstruct.2020.110830
|View full text |Cite
|
Sign up to set email alerts
|

Pushover analysis of unreinforced irregular masonry buildings: Lessons from different modeling approaches

Abstract: The present paper addresses the seismic performance of a half-scale two-story unreinforced masonry (URM) building with structural irregularity in plan and in elevation. The main objectives are (i) to understand the seismic response of URM buildings with torsional effects, and (ii) to evaluate the reliability of using simplified approaches for irregular masonry buildings. For this purpose, nonlinear static analyses are carried out by using three different modeling approaches, based on a continuum model, beam-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 60 publications
(74 reference statements)
0
37
0
1
Order By: Relevance
“…Salonikios et al 2003;Giamundo et al 2014;Betti et al 2014), considering also commercial software packages (e.g. Marques and Lourenco 2011;Calderoni et al 2015;De Falco et al 2017;Siano et al 2018;Aşıkoğlu et al 2020); or blind predictions involving a large number of research teams called to predict the seismic response of the same benchmark prototype (e.g. in Mendes et al 2017;Esposito et al 2019;Bartoli et al 2017;Parisse et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Salonikios et al 2003;Giamundo et al 2014;Betti et al 2014), considering also commercial software packages (e.g. Marques and Lourenco 2011;Calderoni et al 2015;De Falco et al 2017;Siano et al 2018;Aşıkoğlu et al 2020); or blind predictions involving a large number of research teams called to predict the seismic response of the same benchmark prototype (e.g. in Mendes et al 2017;Esposito et al 2019;Bartoli et al 2017;Parisse et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This can be considerably relevant due to the high nonlinearity of masonry. In this respect, the concept of capacity dominium was introduced by [63], and an example of its application is found in [14].…”
Section: Applications On Masonry Buildingsmentioning
confidence: 99%
“…According to [13], numerical strategies available for masonry structures can be categorized as four main groups based on the modeling approach: (i) block-based model,: this uses block elements aiming at considering the real masonry arrangement (units and mortar); (ii) continuum model,: a representative model is taken into account as a continuum deformable body with homogenous material behavior; (iii) macro-element model: the discretization of the model is carried out by panel elements, so-called macro-elements; and (iv) geometry-based model: the description of the model is based on the geometry of the structure only. Several studies have shown that results of the nonlinear static analysis are highly dependent on the numerical procedure adopted to simulate the structure [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Here, the performance-based applications are studied, regardless of the numerical modeling and simulations in the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the Italian Guidelines [8] do not identify the use of a specific modeling approach to perform the EL3 analyses and the selection of the convenient code is left to the judgement of the analyst. Recent study deals with this topic by reporting the results of blind benchmarks for seismic assessment of unreinforced masonry structures which compares different modeling approaches (e.g., [43][44][45]).…”
Section: Third Level Of Analysis (El3)mentioning
confidence: 99%